High risks in African farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Farming in Africa is a gamble, and African subsistence farmers have to do everything in their power to cut down the risks and ensure that their families are fed and provided for. This may explain why they are so cautious about adopting new ideas and...